Peningkatan Hasil Belajar Siswa Menggunakan Pendekatan Saintifik Pada Pembelajaran Tematik Terpdu Di Kelas II SD - Zavina, Zavina; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The purpose of this study is to describe the use of a scientific approach to improve student learning outcomes in integrated thematic learning in class II of SD Pembangunan Laboratorium UNP. This type of research is classroom action research using qualitative and quantitative approaches. The study was conducted in two cycles, consisting of planning, implementing, observing, and reflecting. The results showed an increase in the first cycle of meetings I and II, cycle II. The observations of RPP I cycle I and II meeting, cycle II obtained 72.22% (C), 83.33% (B), 91.66% (SB). Observing aspects of the teacher in the first cycle of meetings I and II, cycle II gained 79.16% (B), 83.33% (B), 95.85% (SB). Observing aspects of students in cycle I meeting I and II, cycle II gained 75% (C), 83.33% (B), 91.66% (SB). Student learning outcomes aspects of the first cycle of knowledge I and II, and the second cycle gained 78.54%, 82.79%, 86.17%. Student learning outcomes aspects of the first cycle of meeting I and II, and the second cycle gained 79.89%, 80.11%, 87.5%. It can be concluded that the use of a scientific approach can improve student learning outcomes. Keywords: Scientific Approach, student learning outcomes.